Cleavage of IgG1 in gingival crevicular fluid is associated with the presence of Porphyromonas gingivalis. (1st November 2012) - Guentsch, A.; Hirsch, C.; Pfister, W.; Vincents, B.; Abrahamson, M.; Sroka, A.; Potempa, J.; Eick, S.
<x xml:space="preserve">Abstract</x> Background and Objectives Immunoglobulin (Ig) G1 plays an important role in the adaptive immune response. Kgp, a lysine‐specific cysteine protease from Porphyromonas gingivalis, specifically hydrolyses IgG1 heavy chains. The purpose of this study was to examine whether cleavage of IgG1 occurs in gingival crevicular fluid (GCF) in vivo, and whether there is any association with the presence of Porphyromonas gingivalis and other periodontopathogens. Material and Methods GCF was obtained from nine patients with aggressive periodontitis, nine with chronic periodontitis and five periodontally healthy individuals. The bacterial loads of Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Treponema denticola, Prevotella intermedia and Tannerella forsythia were analysed by real‐time polymerase chain reaction, and the presence and cleavage of IgG1 and IgG2 were determined using Western blotting. Kgp levels were measured by ELISA. Results Cleaved IgG1 was identified in the GCF from 67% of patients with aggressive periodontitis and in 44% of patients with chronic periodontitis. By contrast, no cleaved IgG1 was detectable in healthy controls. No degradation of IgG2 was detected in any of the samples, regardless of health status. Porphyromonas gingivalis was found in high numbers in all samples in which cleavage of IgG1 was detected (P < 0.001 compared with samples with no IgG cleavage). Furthermore, high numbers of Tannerella forsythia and Prevotella intermedia were also present in these samples. The level of Kgp in the GCF correlated with the load of Porphyromonas gingivalis (r = 0.425, P < 0.01). The presence of Kgp (range 0.07–10.98 ng/mL) was associated with proteolytic fragments of IgG1 (P < 0.001). However, cleaved IgG1 was also detected in samples with no detectable Kgp. Conclusion In patients with periodontitis, cleavage of IgG1 occurs in vivo and may suppress antibody‐dependent antibacterial activity in subgingival biofilms especially those colonized by Porphyromonas gingivalis.